Telomere Length in Workers Was Effected by Omethoate Exposure, GSTM1 Deletion, Interaction Between Smoking and GSTP1 Polymorphisms. Issue 1 (January 2019) - Wang, Wei; Zhang, Hui; Duan, Xiaoran; Feng, Xiaolei; Wang, Tuanwei; Wang, Pengpeng; Ding, Mingcui; Liu, Suxiang; Li, Lei; Liu, Junling; Tang, Lixia; Niu, Xinhua; et al.
Abstract : Objective: The aim of this study was to explore the association between telomere length and metabolizing enzyme gene polymorphisms and environmental factors in omethoate-exposed workers. Methods: The gene–environment interactions were analyzed with generalized linear model method. Results: The relative telomere lengths in the individuals with GSTM1- deletion were longer than that in non-deletion genotype in the control group ( P = 0.011); the relative telomere lengths with GG+AG genotypes in GSTP1 rs1695 were longer than that of AA genotype in the exposure group ( P = 0.039). The interaction between the GG+AG genotypes in GSTP1 rs1695 and smoking exposure had significant effect on telomere length ( P < 0.05). Conclusions: The prolongation of relative telomere length in omethoate-exposed workers was associated with GSTM1- deletion, GG+AG genotypes, and interactions of GG+AG genotypes and smoking factor.